Anthrax Outbreaks in Kyotera District, Uganda: Implications for Public Health Emergency Preparedness - Majani Edward; Francis Ogwang; Samuel Ojera; Francis Obaa (Wiley, 2025)
Introduction In late 2023, Uganda's Ministry of Health declared an anthrax outbreak in the Kyotera district, Masaka region, following reported animal and human fatalities. This article outlines the initial outbreak characteristics and the multi-sectoral response initiated by national and international stakeholders. Methodology This article presents a descriptive account of the anthrax outbreak in Kyotera district based on preliminary investigations, surveillance data provided by the Ministry of Health and collaborating partners (WHO, Infectious Disease Institute, Public Health Fellowship Program, Masaka Regional PHEOC), and a review of the unfolding events up to October 31, 2023. Results The anthrax outbreak in Kyotera district significantly impacted both human and livestock populations, leading to confirmed human cases, fatalities, and the death of 24 animals by October 31, 2023. The outbreak disrupted community livelihoods and strained the healthcare system, particularly as Uganda continues its recovery from the COVID-19 pandemic. Preliminary observations suggest a potential link between the outbreak and the rainy season, consistent with previous anthrax occurrences in East Africa. Economic consequences included potential job losses in the local meat industry and increased demands on healthcare resources. Conclusion The recent anthrax outbreak in Kyotera district underscores the ongoing threat of zoonotic diseases and the importance of a swift, coordinated, and multi-sectoral response. The findings highlight the need for strengthened interministerial cooperation, proactive health education campaigns targeting at-risk communities, consideration of prophylactic interventions, and the adoption of a comprehensive One Health approach for effective prevention and control of future outbreaks in Uganda.
Keywords: anthrax; Kyotera; One Health approach; prevention and control; Uganda; zoonotic diseases